2009
DOI: 10.1002/emmm.200900040
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate induces oxidative DNA damage and is selectively lethal to tumour cells with defects in the DNA mismatch repair gene MSH2

Abstract: Mutations in the MSH2 gene predispose to a number of tumourigenic conditions, including hereditary non-polyposis colon cancer (HNPCC). MSH2 encodes a protein in the mismatch repair (MMR) pathway which is involved in the removal of mispairs originating during replication or from damaged DNA. To identify new therapeutic strategies for the treatment of cancer arising from MMR deficiency, we screened a small molecule library encompassing previously utilized drugs and drug-like molecules to identify agents selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(130 citation statements)
references
References 53 publications
4
123
0
3
Order By: Relevance
“…273 Defects in the mismatch system has been related to inferior response to 5-fluorouracil in cancer of the large bowel, 272 but more lately to an inferior response to cisplatin in germ-cell tumours (testicular seminomas and non-seminomas) as well. 274 In contrast, there is experimental evidence indicating enhanced response to methotrexate-induced oxidative damage in MSH2-deficient endometrial and colon cancer-derived cells, 275 but reduced response to thiopurines in leukemia cells. 276 O 6 -METHYL-GUANINE-DNA-METHYLTRANSFERASE In addition to the mechanisms described above, MGMT has a role in therapy sensitivity.…”
Section: Mismatch Repairmentioning
confidence: 99%
“…273 Defects in the mismatch system has been related to inferior response to 5-fluorouracil in cancer of the large bowel, 272 but more lately to an inferior response to cisplatin in germ-cell tumours (testicular seminomas and non-seminomas) as well. 274 In contrast, there is experimental evidence indicating enhanced response to methotrexate-induced oxidative damage in MSH2-deficient endometrial and colon cancer-derived cells, 275 but reduced response to thiopurines in leukemia cells. 276 O 6 -METHYL-GUANINE-DNA-METHYLTRANSFERASE In addition to the mechanisms described above, MGMT has a role in therapy sensitivity.…”
Section: Mismatch Repairmentioning
confidence: 99%
“…We have previously shown that synthetic lethality with MMR genes can be achieved by causing oxidative DNA damage in an MMR-deficient background (10,16). More specifically, MSH2 deficiency is synthetically lethal with genetic changes that result in an accumulation of 8-oxoG lesions in nuclear DNA (one of the more common oxidized DNA bases that are caused by oxidative damage), whereas MLH1 deficiency is synthetically lethal with genetic changes that cause mitochondrial DNA 8-oxoG accumulation (10).…”
Section: Pink1 Silencing Is Synthetically Lethal With Mmr Deficiency mentioning
confidence: 99%
“…We have applied this approach to MMR-deficient cancers by identifying a synthetic lethal interaction between MSH2 deficiency and treatment with the chemotherapeutic agent methotrexate (45 (45). Similarly, MSH2-deficient cells are sensitive to psoralen, an agent that induces DNA interstrand crosslinks, but MLH1-deficient cells tend to be more resistant (46,47).…”
Section: Synthetic Lethal Targeting Of Mismatch Repair Deficiencymentioning
confidence: 99%